The maine executive levels of consumers satisficing according to ISO 9001 - Хади, Амине (Technology audit and production reserves, 2014)
The adoption of a quality management system should be a strategic decision for an organization. customers relation is a business strategy and it’s level is higher than the amount of grows sales and it’s purpose is not only having more benefit but also client satisficing. All departments one’s organization can be directly or indirectly connected with clients. Each client has a different conceptions to one or a number of organizations. there are a number of methods for handling this matter, the best one is making CRM strategy with the ISO 9001 strategy. In this case study the main executive levels in an organization were described.